Impact of overweight on patients undergoing laparoscopic pancreaticoduodenectomy: analysis of surgical outcomes in a high-volume center - Dechao Li; Shulin Wang; Huating Zhang; Yukun Cao; Qingsen Chu (BMC Surgery)
Abstract Background The feasibility and safety of laparoscopic pancreaticoduodenectomy (LPD) in overweight patients is still controversial. This study was designed to analyze the impact of overweight on surgical outcomes in patients undergoing LPD. Methods Data from patients who underwent LPD between January 2018 and July 2022 were analyzed retrospectively. A 1:1 propensity score-matching (PSM) analysis was performed to minimize bias between groups. Results A total of 432 patients were enrolled, with a normal weight group (n = 241) and an overweight group (n = 191). After matching, 144 patients were enrolled in each group. The results showed that the incidence of clinically relevant postoperative pancreatic fistula (CR-POPF) and delayed gastric emptying (DGE) was significantly higher in the overweight group compared to the normal weight group (P = 0.036). However, there were no significant differences in perioperative mortality (1.4% vs. 2.1%, P = 0.652) and long-term survival outcomes between malignancy patients with different body mass index (BMI) before and after PSM (all P > 0.05). Conclusions It is safe and feasible for overweight patients to undergo LPD with mortality and long-term survival outcomes comparable to the normal weight group. High-quality prospective randomized controlled trials are still needed.